Optimal output-feedback control over Markov wireless communication channels - Impicciatore, Anastasia; Lun, Yuriy Zacchia; Pepe, Pierdomenico; D'Innocenzo, Alessandro (IEEE transactions on automatic control, 2024)
The communication links connecting components of wireless control systems may be affected by packet losses due to time-varying fading and interference. We consider a wireless control network (WCN) with double-sided packet-losses: on the sensor-controller link (sensing link) and controller-actuator link (actuation link). We model the sensing and actuation links as finite-state Markov channels (FSMCs). One time-step delay affects the actuation link mode observation, while the sensing link mode observation is not affected by any delay. In this paper, we solve, as our main contribution, the optimal output-feedback control problem in this FSMC setting (under a TCP-like communication scheme) using two different state estimation techniques: Luenberger observer and current estimator, comparing the two methodologies and deriving a separation principle for both the cases. We also derive detectability conditions guaranteeing the existence of an optimal observer, either Luenberger or current.